Two new species of Aclis (Mollusca: Gastropoda: Aclididae) from the continental slope of northeast Brazil - de Barros, José Carlos N.; de Lima, Silvio Felipe B.; de A. Francisco, Jonata (Zootaxa, 2007)
Two new species of Aclis Lovén, 1846 are described from the continental slope of northeast Brazil. Aclis macrostoma n. sp. is recorded off the state of Rio Grande do Norte at depths ranging from 375 to 510 meters. Aclis watsoni n. sp. was dredged off the state of Sergipe at depths ranging from 365 to 510 meters. There are no similar species along the Brazilian coast. Aclis watsoni is similar to Aclis angulata Smith, 1890, Aclis trilineata Watson, 1897, Aclis supranitida (Wood, 1842) and Aclis ascaris (Turton, 1819) due to the presence of spiral keels and/or indication of a subsutural ramp. Aclis macrostoma is similar to Discaclis canariensis Moolenbeek & Warén, 1987, Aclis attenuans Jeffreys, 1883 and Aclis gulsonae (Clark, 1850) regarding its circular aperture and dilatation of the peristome, with a non-thickened outer lip. The latter two species are much more slender.